Multiple Retinal Axons Converge onto Relay Cells in the Adult Mouse Thalamus - Sarah Hammer; Aboozar Monavarfeshani; Tyler Lemon; Jianmin Su; Michael Andrew Fox (Cell Reports, 2015)
Activity-dependent refinement of neural circuits is a fundamental principle of neural development. This process has been well studied at retinogeniculate synapses—synapses that form between retinal ganglion cells (RGCs) and relay cells within the dorsal lateral geniculate nucleus. Physiological studies suggest that shortly after birth, inputs from ∼20 RGCs converge onto relay cells. Subsequently, all but just one to two of these inputs are eliminated. Despite widespread acceptance, this notion is at odds with ultrastructural studies showing numerous retinal terminals clustering onto relay cell dendrites in the adult. Here, we explored this discrepancy using brainbow AAVs and serial block face scanning electron microscopy (SBFSEM). Results with both approaches demonstrate that terminals from numerous RGCs cluster onto relay cell dendrites, challenging the notion that only one to two RGCs innervate each relay cell. These findings force us to re-evaluate our understanding of subcortical visual circuitry.